Lesbian potentiality and feminist media in the 1970s - Samer, Rox (Duke University Press, 2022)
In Lesbian Potentiality and Feminist Media in the 1970s, Rox Samer explores how 1970s feminists took up the figure of the lesbian in broad attempts to reimagine gender and sexuality. Samer turns to feminist film, video, and science fiction literature, offering a historiographical concept called “lesbian potentiality”—a way of thinking beyond what the lesbian was, in favor of how the lesbian signified what could have come to be. Samer shows how the labor of feminist media workers and fans put lesbian potentiality into movement. They see lesbian potentiality in feminist prison documentaries that theorize the prison industrial complex’s racialized and gendered violence and give image to Black feminist love politics and freedom dreaming. Lesbian potentiality also circulates through the alternative spaces created by feminist science fiction and fantasy fanzines like The Witch and the Chameleon and Janus. It was here that author James Tiptree, Jr./Alice B. Sheldon felt free to do gender differently and inspired many others to do so in turn. Throughout, Samer embraces the perpetual reimagination of “lesbian” and the lesbian’s former futures for the sake of continued, radical world-building.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; cinéma; communication; discipline; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; thématiques; études littéraires

Un cheval de Troie nommé Monique Wittig - Eloit, Ilana (Cahiers du Genre, 2021)
Cet article se propose de lire L’Opoponax , Les Guérillères , Le Corps lesbien et la théorie lesbienne de Monique Wittig, qu’elle forge au tournant des années 1980, au prisme de sa stratégie d’universalisation des points de vue minoritaires. Il démontre que la pensée lesbienne de Wittig n’est pas en rupture avec sa conception du féminisme et de la littérature telle qu’elle se manifeste dans ses premières œuvres littéraires, mais dans la continuité de sa critique de l’appropriation de l’universel par des positions épistémo-logiquement dominantes dans le langage. Il analyse sa trajectoire d’écrivaine, de militante féministe/lesbienne et de théoricienne lesbienne à la lumière de la métaphore du « cheval de Troie » qu’elle emploie pour décrire le travail littéraire.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; discipline; europe; france; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; études littéraires

La pensée straight - Wittig, Monique; Bourcier, Sam (Éditions Amsterdam, 2018)
En 1978, Monique Wittig clôt sa conférence sur « La Pensée straight » par ces mots : « Les lesbiennes ne sont pas des femmes. » L'onde de choc provoquée par cet énoncé n'en finit pas de se faire ressentir, aujourd'hui encore, dans la théorie féministe et au-delà. En analysant l'aspect fondateur de la « naturalité » supposée de l'hétérosexualité au sein de nos structures de pensées, que ce soit par exemple dans l'anthropologie structurale ou la psychanalyse, Monique Wittig met au jour le fait que l'hétérosexualité n'est ni naturelle, ni un donné : l'hétérosexualité est un régime politique. Il importe donc, pour instaurer la lutte des « classes », de dépasser les catégories « hommes »/« femmes », catégories normatives et aliénantes. Dans ces conditions, le fait d'être lesbienne, c'est-à-dire hors-la-loi de la structure hétérosexuelle, aussi bien sociale que conceptuelle, est comme une brèche, une fissure permettant enfin de penser ce qui est "toujours déjà là"
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; approches et analyses; arts; cours; discipline; féminisme matérialiste; har4600; identités LGBTQIA2+; lesbianisme; militance; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; études littéraires

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Le corps lesbien - Wittig, Monique (Éditions de minuit, 1973)
Le lesbianisme est traité selon une dimension poétique : le corps féminin est énuméré selon ses différentes parties, et se présente comme un manifeste de la révolte féminine, écrit par une femme, pour les femmes.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; corps; corps féminin; cours; discipline; europe; fem1000; france; lesbianisme; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires